ANALISIS PRESTASI AKADEMIK PADA MAHASISWA YANG BEKERJA PART-TIME DI JURUSAN EKONOMI PEMBANGUNAN FAKULTAS EKONOMI UNIVERSITAS NEGERI MALANG ANGKATAN 2014 - Glagah Mahestya Yahya; Sri Umi Mintarti (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2019)
This research analyzes how the change of academic achievement of students working part time. Lecture while working among students is not a new thing. The main reason is related to finance and filling free time due to lecture schedule that is not solid. Living college while working is not easy. This will affect the student's academic performance to see the multiple roles performed. This research uses qualitative research approach with type of research of femenologi. Selection of research subjects using snowball sampling method. The technique to be used in data collection in this research consists of three techniques, namely: (1) observation techniques, (2) interview techniques, and (3) documentation techniques. Data analysis techniques in this study consist of the stages of analysts of data penelian covering (1) data reduction, (2) Display data, and (3) Verification and conclusion. Students' academic achievement after part-time work viewed from IPK has decreased but the decrease is not significant. The decline in academic achievement is due to students after work, students have problems related to the difficulty of managing time between college and work.